Determining the prevalence of SCCmec polymorphism, virulence and antibiotic resistance genes among methicillin-resistant Staphylococcus aureus (MRSA) isolates collected from selected hospitals in west of Iran. (3rd March 2016) - Taherikalani, Morovat; Mohammadzad, Mohammad Reza; Soroush, Setareh; Maleki, Mohammad Hossein; Azizi-Jalilian, Farid; Pakzad, Iraj; Sadeghifard, Nourkhoda; Asadollahi, Parisa; Emaneini, Mohammad; Monjezi, Aazam; Alikhani, Mohammad Yousef
Abstract : Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most important pathogens worldwide and compared to other staphylococcal species that are associated with higher mortality rate. A total of 500 Staphylococcus spp. was collected from selected hospitals in Ilam, Kermanshah, Khorram Abad and Hamadan cities and, via phenotypic and genotypic methods, was assessed to find MRSA. The presence or absence of prevalent antibiotic resistance genes and virulence genes was evaluated among MRSA isolates, using polymerase chain reaction (PCR) method, and then the SCCmec typing of these isolates was assayed by multiplex PCR. A total of 372 (74.4%) Stapylococcus spp. isolates were identified as S. aureus, among which 200 (53.8%) possessed the mecA gene and were distinguished as MRSA. All of MRSA isolates contained blaZ gene. The frequency of ermA and ermC genes among erythromycin-resistant MRSA isolates was 21.6% and 66.7%, respectively. The frequency of the virulence genes eta, hla and sea among MRSA isolates was 10%, 80.5% and 100%, respectively. SCCmec type IV accounted for 30.6% of the MRSA isolates and SCCmec type III, SCCmec type II and SCCmec type I accounted for 30%, 22% and 17.5% of the isolates, respectively. The antibiotic resistance genes and the virulence genes of blaZ, hla, sea, eta and ermC had high frequencies among the MRSA isolates. This study showed that the antibiotic resistance genes had higher frequencies among SCCmec types I and IV, which confirms the previous reports in this field.